Perlindungan Hukum Bagi Korban Silent Treatment Sebagai Bentuk Kekerasan Psikis Dalam Rumah Tangga - Rahmawati , Faizatur; Nofitasari, Solehati; Manab, Abd.; Wahyuningtyas, Yuli Winiari; A. Razaq , Moh. Khalilullah (WELFARE STATE Jurnal Hukum, 2025)
This study aims to analyze in depth whether silent treatment can be categorized as a form of psychological abuse as defined in the PKDRT Law, as well as to examine the forms of legal protection available and that can be provided to victims of silent treatment in the context of domestic violence cases. This study uses a normative juridical method that combines a legislative approach and a conceptual approach as the basis for analysis. The results of this study clearly show that silent treatment fulfills the elements of psychological violence because this behavior can cause deep feelings of fear, erode self-confidence, and cause significant mental suffering to the victim. From a legal protection perspective, victims of silent treatment are entitled to adequate health services, psychological and social assistance, and a process of mental recovery. In addition, perpetrators of silent treatment can be subject to criminal sanctions as an effort to enforce the law and protect victims of psychological violence.